Comparison of the Physical and Chemical Properties of the Soil in the Rawagha area of Waddan and the Limestone in Sukna, and the Importance of their uses in the Construction Resort - عبد الله علي عبد الله الحوينط; حسن محمد حسن (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aims to study and analyze the physical and mechanical properties of the soil of the Rawagha Mountains located in the Waddan region, in addition to the limestone in the Sukna region, because these materials are of great importance in engineering applications and the manufacture of building materials. Samples collected from both of the sites and subjected to standard geotechnical tests following ASTM and AASHTO specifications, including sieve analysis (ASTM D6913), standard Proctor compaction (ASTM D698), California Bearing Ratio (ASTM D1883), and Los Angeles abrasion (ASTM C131). Results revealed that the Rawagha soil classified as SP-SM (poorly graded sand with silt) according to USCS, with maximum dry density (MDD) of 1.989 g/cm³ at optimum moisture content (OMC) of 10.7%, and CBR value of 29%. The Suknah limestone aggregate classified as SP (poorly graded sand) with MDD of 2.124 g/cm³ at OMC of 8.0%, and CBR value of 38%. Los Angeles abrasion loss within allowable limits ≤ 40%. The study concludes that both materials are suitable for sub base layers in road construction and general civil engineering applications, if proper moisture control and compaction maintained. The Suknah limestone demonstrates superior mechanical properties compared to Rawagha soil. This study contributes to providing a reliable scientific database for engineering planning and project implementation in the Jufra region, and opens the door for more detailed future studies on soil and rock behavior in arid and semi-arid environments.